The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.isci.2020.101038
|View full text |Cite
|
Sign up to set email alerts
|

ORCA/LRWD1 Regulates Homologous Recombination at ALT-Telomeres by Modulating Heterochromatin Organization

Abstract: Telomeres are maintained by telomerase or in a subset of cancer cells by a homologous recombination (HR)-based mechanism, Alternative Lengthening of Telomeres (ALT). The mechanisms regulating telomere-homeostasis in ALT cells remain unclear. We report that a replication initiator protein, Origin Recognition Complex-Associated (ORCA/LRWD1), by localizing at the ALT-telomeres, modulates HR activity. ORCA's localization to the ALT-telomeres is facilitated by its interaction to SUMOylated shelterin components. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Accordingly, the expression of the TRF2 ΔB mutant form reduces ORI formation in telomeres by disrupting ORC and the replicative helicase MCM3 [ 21 ]. Other properties of TRF2 could also be involved in its role in pericentromeric replication initiation since it was reported that it associates to ORCA/LRWD1 [ 24 ] and that, in addition to the basic N-terminal domain, the TRF2 dimerization domain is required for ORC recruitment [ 25 ]. An interesting possibility would be that the pericentromeric ORI activity also relies on the ability of TRF2 to bind and unwind the formation of a G-quadruplex structure within the G-rich satellite DNA repeats [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the expression of the TRF2 ΔB mutant form reduces ORI formation in telomeres by disrupting ORC and the replicative helicase MCM3 [ 21 ]. Other properties of TRF2 could also be involved in its role in pericentromeric replication initiation since it was reported that it associates to ORCA/LRWD1 [ 24 ] and that, in addition to the basic N-terminal domain, the TRF2 dimerization domain is required for ORC recruitment [ 25 ]. An interesting possibility would be that the pericentromeric ORI activity also relies on the ability of TRF2 to bind and unwind the formation of a G-quadruplex structure within the G-rich satellite DNA repeats [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, TGFBr1 has been shown to regulate C2C12 myoblast proliferation and differentiation by triggering the Smad3 signaling pathway [ 30 , 31 ]. In addition, TGFBs and TGFBRs are reported to be highly associated with myoblast differentiation (including fusion and myogenesis) and as the regulator of MRFs [ 32 , 33 , 34 ]. It has been reported that FGF7 is up-regulated in differentiated myofibers [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These genes all have their known functions linked to chromatin state. For example, LRWD1 is a subunit of the origin recognition complex (ORC) and plays a role in heterochromatin organization and cell cycle control (20)(21)(22)(23). KAT2A (also known as GCN5), a histone acetyltransferase, and SUV39H1, a histone methyltransferase that trimethylates lysine 9 of histone H3, are most highly studied histone enzymes and play pivotal roles in the epigenetic landscape and chromatin modification (24,25).…”
Section: Translational Switch Occurs During Bovine Major Egamentioning
confidence: 99%